Polemik Poligami: Pro dan Kontra Poligami di Indonesia - Apriliani, Devi Rizki (Medpro, 2023)
This study aims to discuss the pros and cons of polygamy among society and scholars in Indonesia. Polygamy, as one of the forms of marriage permitted in Islam, remains a controversial and often debated topic. The study employs a qualitative method with a literature review and content analysis approach. Data sources were gathered from various scholarly literature relevant to the theme of polygamy, which were analyzed to identify differing views on the law and practice of polygamy in Islam. The findings reveal significant differences in opinions between scholars and society regarding the law of polygamy. Some scholars argue that polygamy is permissible under certain conditions, while others emphasize that it should only be practiced in emergency situations. Additionally, it was found that social, economic, and psychological values influence societal views on polygamy. This study contributes to a deeper understanding of the polygamy debate in Indonesia and offers insights for policymakers and academics to consider broader factors in formulating policies related to polygamy. This research provides a comprehensive perspective by combining historical, sociological, and legal analysis of polygamy and highlights the differing opinions among scholars and society.